Transforming mosques into a containment space during natural disasters; browsing through recent publications - Shakir Haraty, Hayder Jawad; Mat Raschid, Mohammad Yazah; Utaberta, Nangkula (Science Publishing Corporation, 2018)
Mosques around the world have been serving the Muslim community for religious and social purposes since the beginning of Islam. Mosques have played an important role to educate and create a peaceful yet proper cosmos for its visitors. However, nowadays, mosques are not only used for its educational component, but on occasion have been transformed into places to serve multi-ethnic and multi-religious communities during natural disasters. This paper is an attempt to surf through the recent publications that discuss natural disasters and the containment of such incidents. Four case studies have been presented to draw a picture of a mosque’s role before, during and after natural disasters. Although many researchers have investigated this role, there still is an urgent need to understand the several examples of cases globally and the issues the researchers have dealt with in such incidents. Selected papers have been reviewed to study the conclusions found in the most recent publications in this field. The aim of this paper is to find out the missing aspects and the gap in the literature for the purpose of future studies and designs.